A decision support system for the technical sustainability assessment of water distribution systems. (May 2015) - Aydin, Nazli Yonca; Zeckzer, Dirk; Hagen, Hans; Schmitt, Theo
Abstract: The purpose of this study is to develop a decision support system (DSS) for the technical sustainability assessment of water distribution systems (WDSs). The technical sustainability is assessed based on the sustainability index methodology using reliability, resiliency, and vulnerability as performance criteria. These performance criteria are visualized by the DSS combining several visualization techniques to improve the raw data readability and the effectiveness of the decision-making process. The technical sustainability of the existing WDS is assessed using the sustainability index methodology and two alternative scenarios are proposed to improve the sustainability. The "new pump" scenario is based on adding network components. The second scenario is based on using reclaimed water for non-potable water demand and fire flow. The results show that the DSS is effective to illustrate time-dependent variables in the WDS and that the sustainability index methodology is a credible approach to compare scenarios and to identify problematic locations. Highlights: We propose a DSS to evaluate the technical sustainability of WDS. The technical sustainability is assessed by reliability, resiliency, vulnerability. We proposed scenario-based solutions to improve the technical sustainability of WDS. The visualization method improves the effectiveness of DSS and data readability. The proposed DSS for WDSs is robust tool to compare sustainability scenarios.